Measuring unmet need for contraception as a point prevalence - Caroline Moreau; Mridula Shankar; Stephane Helleringer; Stanley Becker (BMJ Global Health)
Background This study proposes a framework to address conceptual concerns with the standard indicator of unmet need for contraception. We define new point prevalence measures of current status (CS) unmet need and CS unmet demand, by linking contraceptive behaviours to pregnancy exposure and to women’s future contraceptive intentions. We explore the difference between standard and CS unmet need and estimate the proportion of women with CS unmet demand, who may be more likely to adopt contraception.Methods We use Demographic and Health Survey data from 46 low-income and middle-income countries released between 2010 and 2018. We assess differences in women’s classification between standard and CS unmet need indicators and estimate the percentage of women with CS unmet demand for contraception, defined as the percentage of women with CS unmet need who intend to use contraception in the future.Findings We find substantial country-level differences between standard and CS estimates of unmet need, ranging from −8.3% points in Niger to +11.1% points in Nepal. The average predictive value of the standard measure across the 46 countries for identifying prevalent cases of unmet need is 53%. Regardless of indicator (standard or CS), only half of women with unmet need intend to use contraception.Interpretation The results of this study suggest that the standard measure of unmet need has low predictive value in identifying women with current unmet need. Thus, the standard indicator does not reflect a prevalence estimate of unmet need.